Financial Literacy, Psychological Capital and Social Capital on Entrepreneurial of Organic Rice Farmers in Trawas Sub District, Mojokerto District - Sabil Fajar Fath; Abdul Wahib Muhaimin; silvana maulidah (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Organic agricultural entrepreneurship plays a crucial role in enhancing rural livelihoods and promoting sustainable development. However, the success of farmers in developing entrepreneurial capacity is often influenced by various internal and external factors, such as financial literacy, psychological resilience, and social networks. Understanding how these factors interact is essential to strengthen the competitiveness and sustainability of organic rice farming communities. This study examines the influence of financial literacy, psychological capital, and social capital on entrepreneurship of organic rice farmers in Trawas District, Mojokerto Regency, East Java Province. Objective of this study is to analyze how the interaction between the four variables can affect the entrepreneurial ability of farmers. The research method was conducted through a survey on 100 organic rice farmers using purposive sampling technique. Data were collected through interviews and analyzed using Structural Equation Modeling Generalized Structured Component Analysis (SEM GSCA). The results of the analysis show that financial literacy contributes significantly to entrepreneurship, with an influence of 30%. In addition, psychological capital and social capital contribute 16.5% and 35.2% respectively to entrepreneurship development. Financial literacy not only has a direct impact on entrepreneurship, but also strengthens psychological capital and social capital which play an important role in facing entrepreneurial challenges. However, the effect of financial literacy on entrepreneurship through these two mediating variables is not directly significant.